A Review of the Potential Consequences of Pearl Millet (Pennisetum glaucum) for Diabetes Mellitus and Other Biomedical Applications - Pei JinJin; Umapathy Vidhya Rekha; Vengadassalapathy Srinivasan; Hussain Shazia Fathima Jaffer; Rajagopal Ponnulakshmi; Jayaraman Selvaraj; Veeraraghavan Vishnu Priya; Palanisamy Chella Perumal; Gopinath Krishnasamy (MDPI, 2022)
Diabetes mellitus has become a troublesome and increasingly widespread condition. Treatment strategies for diabetes prevention in high-risk as well as in affected individuals are largely attributed to improvements in lifestyle and dietary control. Therefore, it is important to understand the nutritional factors to be used in dietary intervention. A decreased risk of diabetes is associated with daily intake of millet-based foods. Pearl millet is a highly nutritious grain, nutritionally comparable and even superior in calories, protein, vitamins, and minerals to other large cereals, although its intake is confined to lower income segments of society. Pearl millet contains phenolic compounds which possess antidiabetic activity. Thus, it can be used to prepare a variety of food products for diabetes mellitus. Moreover, it also has many health benefits, including combating diabetes mellitus, cancer, cardiovascular conditions, decreasing tumour occurrence, lowering blood pressure, heart disease risk, cholesterol, and fat absorption rate. Therefore, the current review addresses the role of pearl millet in managing diabetes.